Los «Ejercicios de la Encarnación» de Sor Juana Inés de la Cruz o la forma de cumplir con el protocolo - Del Río Parra, Elena (Dicenda. Estudios de lengua y literatura españolas, 2008)
The «Devote Exercises» written by Sor Juana Inés de la Cruz around 1685-1686 have been considered part of the so called «final abandonment» of the author. But considered in their larger context, it is noticeable how they very much suppress the genre’s characteristic self-denigration, replacing it by a personal rhetoric by which the author modifies generic conventions, thus imposing her own devotional and personal style.